1991
DOI: 10.1037/0735-7028.22.5.393
|View full text |Cite
|
Sign up to set email alerts
|

The Congregation Development Program: Data-based consultation with churches and synagogues.

Abstract: The potential for successful consultation between psychological and religious communities is illustrated through one forum, the Congregation Development Program (CDP). A data-based consultation program, the CDP is designed to help churches and synagogues define their strengths and weaknesses and plan for their futures. Congregation life is assessed through participant observation, interviews with clergy and leaders, and a battery of survey instruments designed specifically for congregations. This information i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…Focus on a higher power (e.g., God) might be the distinguishing factor of religious organizations (Pargament, Falgout et al, 1991). Researchers have theorized that one's concept of God (Gorsuch, 1968;Spilka, Armatas, & Nussbaum, 1964) can impact both coping and well-being.…”
Section: God Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…Focus on a higher power (e.g., God) might be the distinguishing factor of religious organizations (Pargament, Falgout et al, 1991). Researchers have theorized that one's concept of God (Gorsuch, 1968;Spilka, Armatas, & Nussbaum, 1964) can impact both coping and well-being.…”
Section: God Supportmentioning
confidence: 99%
“…Persons experiencing stress are more likely to seek help from religious leaders than from any other professional or counselor (see, e.g., Chalfant et al, 1990). Pargament, Falgout et al (1991) posit that the pastor or religious leader plays a critical role in defining the character of congregational life. Maton (1988) indicated that groups perceived as having capable leaders tend to be composed of members who report more positive group appraisal and well-being.…”
Section: Church Leader Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated above, one of the sub-factors of ER was indeed this extrinsicsocial orientation (Gorsuch & McPherson, 1989;Kirkpatrick, 1989). Pargament and colleagues (Pargament, 1992(Pargament, , 1997Pargament et al, 1991) differentiate these motives for relatively superficial social contacts that characterize the extrinsic-social orientation from more basic drives for intimacy, connectedness, belongingness and social unity. Pargament (1997) further suggests that the social goal of religiosity can also be expressed as a desire to give to others or to make the world a better place.…”
Section: Goals or Functions Of Religiositymentioning
confidence: 99%
“…It seems as if little research has been done with regard to the effect of programmes utilising the involvement of the church community in people's wellbeing (Cowart et al, 1995;Pargament et al, 1991;Rissmeyer, 1992).…”
Section: Introductionmentioning
confidence: 99%